Transplantation with GXHPC1 for Liver Cirrhosis: Phase 1 Trial. Issue 1 (December 2019) - Huang, Ko-Chang; Chuang, Ming-Hsi; Lin, Zung-Sheng; Lin, Yi-Chun; Chen, Chun-Hung; Chang, Chao-Liang; Huang, Pi-Chun; Syu, Wan-Sin; Chiou, Tzyy-Wen; Hong, Zih-Han; Tsai, Yu-Chen; Harn, Horng-Jyh; et al.
Currently, the only effective therapy for cirrhosis of the liver is liver transplantation. However, finding a compatible liver is difficult due to the low supply of healthy livers and the ever-increasing demand. However, stem-cell therapy may offer a solution for liver cirrhosis; for example, GXHPC1 therapy preparation contains adipose-derived mesenchymal stem cells (AD-MSCs) and was developed for the treatment of liver cirrhosis. In our previous report, animal studies suggested that treatment of a diseased liver via GXHPC1 transplantation can abrogate liver fibrosis and facilitate recovery of liver function. In our current human trial, patients with liver cirrhosis were included. Their adipose tissue was harvested from the subcutaneous fat of the abdominal wall during surgery. AD-MSCs were cultured and suspended at a concentration of 100 million cells in 1 ml of physiological saline (i.e., GXHPC1). This human study passed the Taiwan Food and Drug Administration IND inspection and received Phase I clinical trial permission. The trial was conducted with six patients with liver cirrhosis to demonstrate the safety and efficacy of administering GXHPC1. Intrahepatic injection of GXHPC1 did not cause any safety issues in the analysis of adverse drug reactions and suspected unexpected serious adverse reactions, and showed a tendency for improvement of liver function, METAVIR score, Child–Pugh score, MELD score, and quality of life for patients with liver cirrhosis.